Clinical Improvement Following Stroke Promptly Reverses Post-stroke Cellular Immune Alterations - Vogelgesang, Antje; Witt, Carl; Heuer, Christin; Schulze, Juliane; Gellrich, Juliane; von Sarnowski, Bettina; Langner, Sönke; Dressel, Alexander; Ruhnau, Johanna (Frontiers in Neurology, 2019)
Background and Purpose: Stroke induces immediate profound alterations of the peripheral immune system rendering patients more susceptible to post stroke infections. The precise mechanisms maintaining stroke-induced immune alterations (SIIA) remain unknown. High-Mobility-Group-Protein B1 (HMGB-1) is elevated for at least 7 days post stroke and has been suggested to mediate SIIA. Patients with rapid clinical recovery of neurological deficits rarely develop severe infections. We therefore investigated whether rapid neurological recovery (either spontaneous or secondary to neurovascular recanalization therapy) alters the course of stroke-induced immune alterations. National Institutes of Health Stroke Scale (NIHSS) served as surrogate marker for neurological improvement. Methods: Fluorescence-activated cell sorting was used to define leukocyte subpopulations. C-reactive protein (CRP), procalcitonin (PCT), HMGB-1, GM-CSF; IFN-β, IFN-γ, IL-1β, IL-1RA, IL-2, IL-4, IL-5, IL-6, IL-10, IL-12, IL-17, IL-17F, IL-18, TNF-α, MIF, IL-8, MCP-1, MCP-4, MIP-3α, MIP-3β, Eotaxin, soluble IL-6 receptor, E-selectin and P-selectin were analysed by ELISA or Multiplex Assays. Serum miRNA expression changes were analysed by qPCR. Results: Cellular parameters were similar in the improved and non-improved cohort on admission. In patients with rapid clinical recovery absolute and relative leukocyte, neutrophil and lymphocyte numbers normalized promptly overnight. In contrast, HMGB-1 serum levels did not differ between the two groups. 9 miRNA were found to be differentially expressed between improved and non- improved patients. Conclusions: SIIA are detectable on admission of acute stroke patients. While it was assumed that post stroke immunosuppression is rapidly reversed with improvement this is the first data set that shows that improvement actually is associated with a rapid reversal of SIIA demonstrating that SIIA require a constant signal to persist. The observation that HMGB-1 serum concentrations were similar in improved and non-improved cohorts argues against a role for this proinflammatory mediator in the maintenance of SIIA. Serum miRNA observed to be regulated in stroke in other publications was counter regulated with improvement in our cohort.